‘Moving in place’: Drought and poverty dynamics in South Wollo, Ethiopia - Little, Peter D.; Stone, M. Priscilla; Mogues, Tewodaj; Castro, A. Peter; Negatu, Workneh (Informa UK Limited, 2006)
This article discusses the impact of drought on poverty dynamics in the South Wollo area of northeastern Ethiopia. Using both survey and anthropological/qualitative data covering a six-year period, the paper assesses which households were able to hold on to assets and recover from the 1999–2000 drought and which were not.